Yield and quality of hybrid tomato grafted and cultivated under shade mesh and greenhouse - Reyes Cabrera, Antonio; Vobledo Torres, Valentin; Valdez-Aguilar, Luis Alonso; Cabrera-de la Fuente, Marcelino; Ramírez-Godina, Francisca; Sandoval-Rangel, Alberto (Ecosistemas y Recursos Agropecuarios, 2018)
The objective was to determine the yield, fruit quality and root development of four grafted tomato hybrids grown under anti-aphid mesh cover and greenhouse. The grafted hybrids were grown under shade mesh and greenhouse from april to november 2014. Variables evaluated were: fruit weight per plant, number of clusters per plant, number of fruits per plant, polar and equatorial fruit diameter, vitamin C and lycopene contents, and root fresh and dry weight. Hybrids grafted and cultivated under anti-aphid mesh had higher quality than the production obtained under greenhouse. However, lycopene and vitamin C contents and accumulated root system dry matter are greater under greenhouse.